The Role of Physical Education, Sports, and Health Subject Teacher Deliberations for Junior High Schools in Bandar Lampung City in Supporting Teacher Competence (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
This research is motivated by previous research which states that the Subject Teacher Deliberation (MGMP) has a strategic role in increasing teacher competence. The purpose of this study was to analyze how the strategy of Teacher Consultation for Physical Education, Sports and Health in Bandar Lampung City Junior High Schools supports teacher competency in the form of; pedagogical, personality, social and professional competence. The approach used in this research is a qualitative approach. A qualitative approach is used to capture the deepest meaning of an event, symptom, fact, event, reality or problem and not to prove a cause-and-effect relationship. The analytical method used in this study adopts Freddy Rangkuti's theory of the SWOT analysis method, Strengths, Weaknesses, Opportunities and Threats. The results of the study showed that the strategy of Teacher Consultation for Physical Education, Sport and Health for Junior High Schools in Bandar Lampung City was in supporting teacher competency; 1).Pedagogic competence it is carried out through teaching training activities between peers (micro teaching), collaborative learning activities (lesson study), Classroom Action Research (PTK) training activities and curriculum training, 2).Personality competence it is carried out through guidance on regulation of the national minister of education concerning teacher competency standards, 3).Social competence it is carried out through brainstorming activities, comparative studies and communication training and 4).Professional competence it is carried out through routine discussion activities to deepen subject matter, common perceptions of subject matter and Professional Development activity programs Sustainable (PKB). Conclusion; choosing the right alternative strategy for the Teacher Consultation for Physical Education, Sports and Health for Junior High Schools in Bandar Lampung City in supporting teacher competence, including; 1).Pedagogic competence is through SO (Strength-Opportunities) strategy, 2).Personality competence is through WO (Weakness-Opportunities) strategies, 3).Social competence is through SO (Strength-Opportunities) strategies and 4).Professional competence namely through the SO (Strength-Opportunities) strategy.